The Effect of The Solvent-To-Leaf Ratio in The Extraction Process of Moringa leaves on Erythrocyte and Lecocyte of Tilapia - Yadin, Yadin; Abidin, Zaenal; Azhar, Fariq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tilapia (Oreochromis niloticus) is a freshwater aquaculture fish that has a fairly high economic value among the Indonesian people. The purpose of this study was to determine the effect of the ratio between the number of moringa leaves and the extracting solution in the extraction process on total lekocytes and total erythrocyte of tilapia. The research was designed in a completely randomized design (CRD) with 5 treatments, namely the comparison of the number of moringa leaves and water solvents. The treatments are control (A), without extract), moringa leaves 5 gr + 10 ml solvent (B), moringa leaves 40 gr + 10 ml solvent (C), moringa leaves 70 gr + 10 ml solvent (D), and moringa leaves 100 gr + 10 ml solvent (E). Each solution was added to the feed as much as 50 ml / 30 grams and given to the fish for 16 days. Erythrocytes and leukocytes were counted on day 0, day 1, day 2, day 3, day 7 and day 16. The results showed that the addition of moringa leaf extract solution in feed affect (P<0.05) the total erythrocytes and total leukocytes in the first day until the 16th day of administration. The best observation results were shown in the addition of 5 g moringa leaf extract solution dissolved with 10 ml of water.